Transformasi Digital Sistem Informasi Pemerintah Daerah dalam Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Keuangan Pemerintah Daerah di BAPENDA Prov. KALTENG - Christop Dwi Putra; Meitiana Meitiana; Nazareno Nazareno; Rengga Andika Putra Herlambang (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Digital transformation in regional financial management is a strategic agenda to realize good governance in Indonesia. This study aims to analyze the implementation of the Regional Financial Information System (SIKD) and the Regional Government Information System (SIPD) in increasing transparency and accountability of financial management at the Regional Revenue Agency (BAPENDA) of Central Kalimantan Province. Using qualitative methods and a systematic literature review approach, this study analyzes various studies related to the digital transformation of regional finance in Indonesia during the period 2019-2026. The results of the analysis show that the implementation of SIKD/SIPD significantly contributes to increased transparency through access to real-time information, strengthening accountability through digital trail audits, and financial management efficiency. However, challenges such as limited human resource competencies, uneven technological infrastructure, and resistance to change remain major obstacles. This study concludes that the success of digital transformation requires synergy between technological aspects, institutional capacity, and leadership commitment to realize transparent, accountable, and sustainable regional financial management.